Investigation Study of Relationship between Thyroid Hormones and Kidney Disorders in Iraqi Kidney Failure Patients - Jasim, Aziz H. (American Journal of Biomedicine and Pharmacy, 2024)
Background: Early in the course of kidney failure, bone abnormalities and resorptions were noted. This led to studies that looked at thyroid hormones (tetra iodothyronine (T4), triiodothyronine (T3), and serum calcium (Ca+2) levels to determine the incidence and severity of skeletal problems in individuals with chronic renal failure (CRF). Methods: A control group of 55 healthy individuals and 55 patients (40/40 male and female) with chronic kidney disease (mean glomerular filtration rate, or GFR) of ˂ 15 ml/min were included in the study. Results: When compared to the control group, the more severe stages of renal failure were associated with a highly significant decrease in thyroid hormones (T3, T4) and a highly significant increase (P ̃ 0.001) in Ca+2 levels. Additionally, the findings indicated that T3 and T4 had high positive relationships (r = 0.801). Additionally, the data indicated a significant negative association (-0.911, -0.800) between T3 and Ca+2 and T4 and Ca+2. Conclusion: there is a strong correlation between kidney diseases and the levels of serum Ca+2 and thyroid hormones (T3, T4).